ANALISIS KAPASITAS INFILTRASI LAHAN PERTANIAN DI SUB DAS KALISARI, MALANG - Nita, Istika; Ayuningtyas, Priska; Prijono, Sugeng; Putra, Aditya Nugraha (Jurnal Tanah dan Sumberdaya Lahan, 2024)
Watershed hydrological conditions can decrease due to changes in land use and inappropriate land management. One of the watershed functions is providing water availability for agricultural areas. Along with the increasing area of agricultural land, there is often the issue of water availability, which has implications for the low opportunity for plants to use it. Infiltration is the initial process of water entry into the soil, so the availability of water is greatly influenced by this process. Agricultural land in the Kalisari sub-watershed is dry land and is dominated by dry fields. The area of the Kalisari sub-watershed has an area of ±5,000 ha divided into 5 land uses, namely mahogany-coffee agroforestry, pine-coffee agroforestry, scrub, dry land, and paddy fields. Infiltration measurements were spread over 43 measurement points, with the observed parameters being texture, bulk density, porosity, permeability, aggregate stability, and soil organic matter. The infiltration rate for all land uses is very fast (>25 cm hour-1), ranging from 12.00 cm hour-1 to 74.37 cm hour-1. The infiltration rate for all land uses was not significantly different; this was in line with soil properties, which included texture, bulk density (0.61-1.02 g cm-3), porosity (51.02-68.06%), permeability (4.88–6.79 cm hour-1), aggregate stability (2.11–3.34 mm), and organic matter (1.61-4.06%). However, the infiltration rate at the study site had a significant relationship with clay (r = -0.77), sand (r = 0.64), silt (r = 0.52) and soil organic matter   (r = 0.48).